Technology Transfer through Frontline Demonstrations on Jute (Indian Journal of Extension Education, 2010)
The study was conducted at Central Research Institute for Jute and Allied Fibres (CRIJAF), Barrackpore with 131 farmers from different categories of eight villages of two jute growing district viz., North 24 Parganas and Hogly in West Bengal. Frontline demonstration (FLDs) were conducted on high yielding jute varities with recommended package of practices on the farmers’ fields. The data were collected through personal interviews, group discussion and empirical observations with the help of semi-structured interview schedule and field record, which compared with farmers practice (FP), commonly undertaken by the local farmers in this region. Results revealed that the technologies emanated through timely and systematic management of the improved cultivation practices has on edge over farmers’ practice by increasing the fibre yield up to 15.67 per cent, additional returns up Rs. 5871 /ha and incremental benefit cost ratio of 1:0.13 on additional expenditure cost Rs. 868 /ha. There was scope to reduce cost of cultivation by the introduction of inechanization, wherever possible and chemical weed control. Farmer perceived the results of FLDs as encouraging over their own practice. Thus, forntline demonstration was found an effective tool for technology transfer by building confidence of the praticipating farmers through technology demonstration on their field.